Amaranthus: an additional cash crop for arid Gujarat - Vyas, S P (Indian Farming, 2015)
It is expected that the population of country may touch 1,363 million by 2025, which will need additional food. The exploitation of under utilized crops and arid lands offer good opportunity in this direction. The information presented suggest that successful cultivation of grain amaranthus in desertic land can add to food security and help to ameliorate the economic condition of the desert dwellers.